Overall Equipment Effectiveness in Coal Mining Company: A Case Study - Nurul Retno Nurwulan (Faculty of Economics and Business, Jenderal Soedirman University, 2020)
An increase in productivity is one of the measures of development in a company. High productivity could increase revenue and profit that can be used to further develop the company. This study was conducted in PT XYZ, one of the biggest coal mining companies in East Kalimantan. The aim of this study was to analyze the productivity of excavators and dump trucks using overall equipment effectiveness (OEE). Based on the calculation, the actual availability and quality of both loading and hauling equipment exceed the targeted values. However, the actual performance is lower than the target. As for the OEE values, all of the equipment have lower actual OEE except Hitachi EX-2500. The lowe OEE values might happen because of bad weather, machine breakdown, and a long queue in the mining area. Based on the analysis results, it is recommended that the company increase the availability, performance, and quality of equipment with the high deviation between actual and targeted values.